CORPORATE BUSINESS ENVIRONMENT AS A SET OF ECONOMIC CONDITIONS FOR BUSINESS DEVELOPMENT - Svetlana A. Gusar (Статистика и экономика)
Intellectual resources are widely used in the formation of corporate business environment. This environment is a new phenomenon in the system of socio-economic relations. The corporate business environment is a set of economic conditions for the development of entrepreneurship, business life. In this environment, exercise more incentives to work, increasing the level of economic freedom, including the freedom of movement of the resource, including intellectual, production components. It is therefore important and necessary to give its definition from the perspective of both economic and organizational-administrative relations, which is a key objective of this research. In addition, the article carried out a comprehensive assessment of how the corporate environment for the development of regional business and knowledge of the mechanisms of the effect of factors internal and external environment for the development of corporate business environment.